Epidemiology of familial sarcoidosis in the UK. Issue 9 (1st September 2000) - McGrath, D S; Daniil, Z; Foley, P; du Bois, J L; Lympany, P A; Cullinan, P; du Bois, R M
Abstract : BACKGROUND: The last comprehensive epidemiological studies on familial sarcoidosis in the UK were more than 25 years ago, reporting another affected family member in 1.7% of index cases. A significant proportion of like-sex over unlike-sex pairs, an excess of mother-child over father-child associations, and a preponderance of monozygous over dizygous twins was noted. Another study reported ethnic heterogeneity in familial disease. This study was undertaken to identify the risk ratio (λS ) for siblings of familial sarcoidosis in the UK, to determine if the previous epidemiological findings have persisted, and to reassess whether ethnic heterogeneity prevails in familial disease. METHOD: Questionnaires were sent to 406 index patients. RESULTS: Two hundred and sixty eight replies (66%) were received. Twenty four of the original 406 index patients (5.91%) were found to have at least one other relative (first, second or third degree) with biopsy proven sarcoidosis. A λS value of 36–73 was calculated indicating significant familial clustering of the disease. Ethnically the families comprised 62.5% Caucasian, 29.2% Afro-Caribbean, and 8.3% Asian. Mean age at diagnosis was 39.8 years for women and 40.9 years for men with a male to female ratio of 1:1.7. This differed for the Asian families in which all the affected members were male. Three sets of female twins (two monozygous and one dizygous) were included. There was an equal distribution of like-sex (primarily female) and unlike-sex families as well as mother-child and father-child pairs. Pulmonary involvement was predominant irrespective of ethnicity, as was the need for corticosteroid treatment. CONCLUSIONS: These results support the theory that a shared determinant (either genetic or environmental) is operating in familial sarcoidosis and suggest that this determinant is similar for all ethnic groups.